INVESTIGATING TAX CULTURE OF THE TAX PAYERS OF THE IRANIAN TAX ADMINISTRATION - Asgharpour , Leila; Pourkiani, Masoud; Jalaee , Sayyed (Revista Inclusiones, 2019)
The purpose of this study is to investigate the tax culture of tax payers in the Iranian Tax Administration. This was an applied-descriptive survey study. The statistical population was divided into three groups according to the share of tax revenue in 2017 and 12 provinces from 31 provinces selected by cluster and quota sampling. The sample size was calculated using the Cochran formula for a large population of 690 people for each group. A questionnaire was used to collect data. The content validity of the questionnaires was confirmed by the experts and the construct validity was verified by factor analysis. The reliability of the questionnaires was also calculated using Cronbach's alpha (0.925). The data were analyzed using correlation coefficient, mean test and factor analysis using the Structural Equation Modeling in LISREL. The results showed that each of the components of the tax culture of the tax payers was higher than satisfactory.